Infant burn injuries related to water heating for powdered infant formula preparation - Chiang, Katelyn V.; Anstey, Erica H.; Abrams, Steven A.; Perrine, Cria G. (Frontiers in Pediatrics, 2023)
Background: Guidance for preparing powdered infant formula (PIF) helps to ensure it meets the nutritional needs of infants and is safe to consume. Among safety concerns is Cronobacter sakazakii contamination which can lead to serious infections and death. PIF preparation guidance varies; there is a lack of consensus on whether there is a need to boil water to inactivate potential Cronobacter and for how long to let the water cool before reconstitution. We sought to quantify the burden of burn injuries among infants related to water heating for PIF preparation. Estimating this burden may help inform preparation recommendations. Methods: Burn injuries among infants <18 months of age were identified from 2017-2019 National Electronic Injury Surveillance System data collected from sampled hospital emergency departments. Injuries were classified as related to PIF water heating, potentially related to PIF water heating but with undetermined causation, related to other infant feeding aspects, or unrelated to infant formula or breast milk feeding. Unweighted case counts for each injury classification were determined. Results: Across sampled emergency departments, 7 PIF water heating injuries were seen among the 44,395 injuries reported for infants <18 months. No reported PIF water heating injuries were fatal, but 3 required hospitalization. Another 238 injuries potentially related to PIF water heating but with undetermined causation were also seen. Conclusion: Preparation guidance should consider both the potential risk for Cronobacter infection and the potential risk for burns.